PENGEMBANGAN STRATEGI BERTAHAN UMKM BATIK DI KOTA SEMARANG PADA MASA PANDEMI COVID-19 - Mohamad Hasanudin; Ardian Widiarto; Alvianita Gunawan Putri; Tutik Dwi Karyanti; Maria Theresia Heni Widyarti (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
The impact of the COVID-19 pandemic on MSME entrepreneurs was felt in the Semarang. The MSME clusters most affected by the COVID-19 pandemic are the Milkfish, Culinary and Batik clusters. Especially for the Batik MSMEs cluster in Semarang City before the crisis caused by Covid 19, the business conditions of the Batik MSMEs in the batik village have also experienced a decline in sales. The business development strategy can be applied as one of the MSME survival strategies, especially for Batik MSMEs. The research method used in this study is qualitative analysis with exploratory steps with participatory observation techniques. This study uses SWOT analysis as a tool used in formulating strategies to survive in the midst of this pandemic by using a list of questionnaires. The results of the survey that have been carried out show that during the COVID-19 pandemic which began to spread in Indonesia in early 2020 until now, Semarang batik craftsmen experienced a very significant decline in turnover. From the survey data, it can be seen that there are 47% of Semarang batik artisans who experienced a decrease of 81% even up to 100%, while the lowest decline in turnover of 21% to 40% was experienced by 6% of respondents as Semarang batik artisans. From the perspective of Porter's Competitive Power Model, the Semarang Batik Cluster MSMEs business actors have problems in terms of traditional competitors, where their traditional competitors are fellow Semarang batik entrepreneurs. The next problem is the presence of newcomers, during this pandemic it is not uncommon for people who are laid off from their jobs or experience business setbacks to try to find new business opportunities to cultivate